Association of Trigeminal Neuralgia and Diabetes Mellitus: A Retrospective Study - Fatemeh Lavaee; Zahra Ranjbar; Ali Mohammad Shahim; Fateme Zarei (Islamic Azad University, 2022)
Objectives: This study aimed to evaluate the relationship of diabetes mellitus (DM) and trigeminal neuralgia (TN) in order to provide new insight for TN pathogenesis. Materials and Methods: This retrospective cross-sectional study compared the prevalence of DM in patients with TN and healthy controls without TN during 2007-2018. Totally, 193 participants were enrolled in the patient and control groups. These participants were selected among patients referred to the Oral and Maxillofacial Medicine Department of Dental School of Shiraz University of Medical Sciences. The age and gender of patients were matched in the two groups. DM (types 1 and 2) was diagnosed based on patient reports and routinely requested lab tests (fasting blood sugar, 2-hour post-prandial). The odds ratio (OR) and Chi-square test were used to compare the mean values. Results: The prevalence of DM in TN patients and control group was 11.4% and 9.8%, respectively. The mean age of the participants was 56.96±13.66 and 56.46±13.47 years in the TN and control groups, respectively. The difference in TN prevalence between the two groups was not significant (P=0.62). Conclusion: Although the prevalence of DM in patients with TN was higher than the control group, this difference was not significant (P>0.05). Women with TN showed DM 25% more than men with TN.